On the dynamics of international stock market efficiency - Mohammed S. Khaled; Stephen P. Keef (Cogent Economics & Finance, 2014)
The Granger causality procedure is used to assess the dynamics of market efficiency of 17 international stock indices. These indices are based on relatively smaller firms. The reference of market efficiency is a stock index, from the same economy, which is based on relatively larger firms. There is evidence that market efficiency increases over time at a decreasing rate.
Keywords: G14; G15; 330; market efficiency; international; stock indices; panel model; Granger causality